اکبر الہ آبادی کی شاعری میں تحسینِ اردو زبان: Urdu Language Appreciation in the Poetry of Akbar Allahabadi - Ali Hassan,; Dr.Muhammad Saeed, (Tashkeel e Jadeed, 2025)
This study delves into the poetic works of Akbar Allahabadi, exploring the appreciation of the Urdu language within them. Akbar Allahabadi has addressed the Urdu language and its issues through diverse methodologies. He articulated that under the dominance of the English language; Urdu can’t remain preserved from its influence. Simultaneously, he stated that debates regarding the Urdu-Hindi conflict are futile. However, his stance emphasized that without giving central importance of Urdu language in the system, national progress is not possible. Additionally, he highlighted the deep impact of local languages on the Urdu language and emphasized the elimination of Persian’s official status as a reason for these influences. In Akbar’s era, Urdu language, due to linguistic deficiencies, distanced itself from meaning, a direct subject of concern for Akbar. He not only articulated the issues of the Urdu language but also made efforts towards their resolution.